PENINGKATAN MINAT BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN MELALUI MEDIA A-SWAY JITU - Sri Cahyati; Deddy Chrisdiarto (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2021)
The unpreparedness of educators in online learning has a significant impact on students' interest in learning. This causes learning to be monotonous, does not spark the enthusiasm of students, even seems to only give online assignments (via email or whatsapp) because they are not yet skilled in using technology for learning purposes. The purpose of writing this article is to find out how much impact the use of A-Sway JITU media has on students' learning interest in the learning process of Pancasila and Citizenship Education (PPKn) at Senior Hight School two Bandung. The method used in data collection is through Classroom Action Research (CAR) with the subject of class XI MIPA 6 with a total of 36 students. The research design used is the Kemmis and Taggar model which includes planning, action, observation, and reflection. Data collection techniques used are observation, tests, and documentation. The data analysis used was descriptive qualitative. The results of this study indicate that there is an increase in students' interest in learning seen from the percentage of learning activities before and after using A-Sway media, and filling out questionnaires before and after the action. This can be seen from the increase in students' interest in learning from 28% pre-cycle activities, in the first cycle to 44% and in the second cycle to 100%. In addition, students who initially scored below the KKM were 26 people, in the first cycle there were 10 people, and in the second cycle zero people. Keywords: A-Sway Correct, Discovery Learning, Interest in Learning, Civics Learning, Students